Evaluating Key Biomotor Abilities: A Comparison between National and International Elite Tennis Players - Pratham Singh; Dharmander Kumar; Mohit Morya; Rishabh Singh; Md. Hamidur Rahman (Physical Education Theory and Methodology)
Background. Biomotor ability is essential for elite tennis players, as it significantly contributes to increased efficiency, responsiveness and overall performance on the court.